2017
DOI: 10.1002/cbin.10887
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional features of lysine acetylation of plant and animal tubulins

Abstract: The study of the genome and the proteome of different species and representatives of distinct kingdoms, especially detection of proteome via wide-scaled analyses has various challenges and pitfalls. Attempts to combine all available information together and isolate some common features for determination of the pathway and their mechanism of action generally have a highly complicated nature. However, microtubule (MT) monomers are highly conserved protein structures, and microtubules are structurally conserved f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…In general, post-translational modifications of tubulin, such as acetylation, de-tyrosination, and phosphorylation, play important roles in regulating the stability and function of microtubules [41]. α-Tubulin acetylation is among the most common modifications [42] and is considered to be a marker of stable microtubules and resistant to turnover [43]; although, tubulin acetylation has been also found on dynamic microtubules [25]. It is suggested that tubulin acetylation weakens lateral interactions between protofilaments, thus “softening” microtubules and increasing their flexibility [44].…”
Section: Discussionmentioning
confidence: 99%
“…In general, post-translational modifications of tubulin, such as acetylation, de-tyrosination, and phosphorylation, play important roles in regulating the stability and function of microtubules [41]. α-Tubulin acetylation is among the most common modifications [42] and is considered to be a marker of stable microtubules and resistant to turnover [43]; although, tubulin acetylation has been also found on dynamic microtubules [25]. It is suggested that tubulin acetylation weakens lateral interactions between protofilaments, thus “softening” microtubules and increasing their flexibility [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying structural and functional relationships of these molecular mechanisms require more research. Computational and biophysical approaches are viable options for analyses of target molecules to understand their interactions and dynamics that initiate biochemical and physiological responses of plants (Wan et al, 2015;Konda et al, 2018;Moffett and Shukla, 2018;Rayevsky et al, 2019;Jha et al, 2022). These responses in turn control plant tolerance and resistance to sub-optimal environmental conditions.…”
Section: Editorial On the Research Topic Structural Bioinformatics An...mentioning
confidence: 99%
“…Besause MTs are highly conserved protein structures, the interaction of MT elements with MT‐associated proteins and post‐translational modifiers is fully dependent on protein interfaces, and almost all MT modifications are well described except acetylation. The paper of Raevsky et al () describes the application of computational methods and comparative analysis of binding modes generated a robust predictive model of acetylation of the ϵ‐amino group of Lys40 in α‐tubulins. As it was demonstrated, the surfaces and amino acid sequences of tubulin homologues from Arabidopsis thaliana are very similar to those from Homo sapiens.…”
Section: Tubulin Acetylationmentioning
confidence: 99%